Application of the Rocchio Relevance Feedback Method to the Book Catalog Search System at the 02 Kaur State Senior High School Library - Jefry Thomas; Asnawati Asnawati; Devi Sartika (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
So far, at the SMA Negeri 02 Kaur Library, there are no facilities that can help students in finding books provided by the library, so if students want to find books, they must do it manually, namely by looking at the bookshelves available in the library or asking questions. directly to the librarian. The book catalog search system at the 02 Kaur State Senior High School Library was created to facilitate the process of searching for books in the library, where in the search process the Rocchio Relevance Feedback method has been applied which is used to analyze keywords into several tokens to be matched into the application database. The application can display the output of book data reports and search results that make it easier for the library to archive reports. With this book search system, it can make it easier for users to find books and find out where the books are on the shelves. Based on the results of black box testing, the functionality of the book catalog search system at the SMA Negeri 02 Kaur Library has been running properly and is able to display book search results based on the desired keywords.